Analisis Risiko K3 dengan Metode HIRADC pada Industri Kepelabuhan di Jawa Timur - Kevin Antorio Ferdicha; Yayok Suryo Purnomo (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2023)
As a company engaged in ports such as ship services, goods services, container services, passenger services, and various services related to the port and shipping industry, of course, prioritizing good service. Various activities in the work environment have potential risks that must be identified and evaluated. Systematic, thorough, and structured approaches such as Hazard Identification, Risk Assessment, and Determine Control or HIRADC are used to identify problems affecting work processes and risks associated with existing equipment or systems, which can endanger individuals around the port. This research was conducted qualitatively by analyzing the safety risks of workers at ports around Surabaya, East Java. The results showed that there were 7 types of work with 45 hazard risks identified.